2011
DOI: 10.1371/journal.pgen.1001303
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcript Profiling of Endosperm without Paternal Contribution Identifies Parent-of-Origin–Dependent Regulation of AGAMOUS-LIKE36

Abstract: Seed development in angiosperms is dependent on the interplay among different transcriptional programs operating in the embryo, the endosperm, and the maternally-derived seed coat. In angiosperms, the embryo and the endosperm are products of double fertilization during which the two pollen sperm cells fuse with the egg cell and the central cell of the female gametophyte. In Arabidopsis, analyses of mutants in the cell-cycle regulator CYCLIN DEPENDENT KINASE A;1 (CKDA;1) have revealed the importance of a patern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 90 publications
6
88
2
Order By: Relevance
“…Nevertheless, our study adds LRE to a growing list of MEGs whose loss negatively impacts seed development, including ZIX, FH5, and NUWA in Arabidopsis (Ingouff et al, 2005;Fitz Gerald et al, 2009;Ngo et al, 2012;He et al, 2017) and MEG1 in maize (Gutiérrez-Marcos et al, 2004;Costa et al, 2012). Additionally, mutations in MEGs like FWA and AGL36 do not result in endosperm phenotypes (Kinoshita et al, 2004;Shirzadi et al, 2011). These MEGs highlight the need to explore alternative theories for imprinting.…”
Section: Silencing Of the Paternal Allele Of Lre May Be Controlled Bymentioning
confidence: 76%
“…Nevertheless, our study adds LRE to a growing list of MEGs whose loss negatively impacts seed development, including ZIX, FH5, and NUWA in Arabidopsis (Ingouff et al, 2005;Fitz Gerald et al, 2009;Ngo et al, 2012;He et al, 2017) and MEG1 in maize (Gutiérrez-Marcos et al, 2004;Costa et al, 2012). Additionally, mutations in MEGs like FWA and AGL36 do not result in endosperm phenotypes (Kinoshita et al, 2004;Shirzadi et al, 2011). These MEGs highlight the need to explore alternative theories for imprinting.…”
Section: Silencing Of the Paternal Allele Of Lre May Be Controlled Bymentioning
confidence: 76%
“…3) [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Comparison of the obtained data with trans-factors identified by the in silico searches of S. miltiorrhiza CPS promoter showed no common protein (Tab.…”
Section: '-Cgtgggccaac-caaaaagg-3'mentioning
confidence: 89%
“…The results of in silico searches and microarray co-expression studies differ with regard to plant morphogenesis. While the in silico studies suggest that CPS promoter has a potential role in plant embryogenesis and leaf development, the microarray co-expression tests indicate that the CPS promoter has potential participation in a broader range of morphogenesis processes as pollen, sieve, seed, ovule, and gametophyte development [25,28,[44][45][46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AGL proteins, such as AGL62, play an important role in endosperm development (Kang et al, 2008;Shirzadi et al, 2011), and differential regulation of AGL genes is associated with deleterious effects in interspecific-interploidy Arabidopsis hybrid fitness (Josefsson et al, 2006;Walia et al, 2009). We found that 10 AGLs, including the previously documented endosperm cluster, were differentially expressed between the Col-0 hybrid and C24 hybrid seed (see Supplemental Table 8 online).…”
Section: Investigation Of Agl Proteinsmentioning
confidence: 99%